Molecular Diagnostics in Tomato: Chip Digital PCR Assays Targeted to Identify and Quantify Clavibacter michiganensis subsp. michiganensis and Ralstonia solanacearum in planta - Caterina Morcia; Isabella Piazza; Roberta Ghizzoni; Valeria Terzi; Ilaria Carrara; Giovanni Bolli; Giorgio Chiusa (Horticulturae, 2023)
Clavibacter michiganensis subsp. michiganensis (Cmm) and Ralstonia solanacearum (Rs) are important bacterial pathogens of tomatoes (Solanum lycopersicum), are included in A2 list in the EPPO (European and Mediterranean Plant Protection Organization) region and are recommended for regulation as quarantine pests. The control of quarantine pathogens requires accurate and rapid detection tools. In this study, a method based on chip digital PCR (cdPCR) was developed to identify and quantify Cmm and Rs. The assays were tested on pure bacteria samples and on tomato samples naturally contaminated or spiked with bacteria DNA. For a better estimation of infection level in host plants, duplex assays that are able to simultaneously amplify plant and bacteria DNA were developed. The two cdPCR assays proposed can be used for the rapid and timely detection of this group of high-risk quarantine bacteria to prevent the spread of pathogens and the occurrence of disease in other areas.